CD8+ T Cells as Multitasking Cells in Immunotherapy: A Review Update (Bangladesh Journal of Medical Microbiology, 2024)
CD8+ T cells, referred to as cytotoxic T lymphocytes (CTLs), play a pivotal role in adaptive immunity, particularly in combating viral infections and malignancies. CD8 T cells, derived from bone marrow progenitors and matured in the thymus, play an essential role in immune defense through their cytotoxic activity. These cells are distinguished by their ability to recognize and eliminate cells that present specific antigens via the major histocompatibility complex (MHC) class I molecules. Upon activation by antigen recognition, they proliferate and differentiate into effector cells capable of eliminating infected or abnormal cells.CD8+ T cells develop in the thymus and express the CD8 co-receptor, which interacts specifically with MHC class I molecules. When a naïve CD8+ T cell encounters an antigen-presenting cell (APC) displaying an antigen bound to MHC class I, it undergoes activation, clonal expansion, and differentiation into cytotoxic effector cells. The primary function of these cells is to eliminate infected or malignant cells by inducing apoptosis through the release of cytotoxic granules containing perforin and granzymes or by engaging death receptors on target cells. Over the past few decades, CD8+ T cells have garnered significant attention for their potential in immunotherapy, particularly in cancer treatment. This review highlights the multifaceted roles of CD8+ T cells in immunotherapy, their mechanisms of action, and the challenges associated with harnessing their full potential.Bangladesh Journal of Medical Microbiology, January 2024;18(1):50-55